Design, synthesis, and biological evaluation of N-arylpiperazine derivatives as interferon inducers - Chu, Yeonjeong; Raja Sekhara Reddy, B.; Pratap Reddy Gajulapalli, V.; Sudhakar Babu, K.; Kim, Eunha; Lee, Sanghee (Bioorganic and Medicinal Chemistry Letters, 2020)
Type I Interferon (IFN) signaling plays an important role in the immune defense system against virus infection and in the innate immune response, thus IFNs are widely used as anti-viral agents and treatment for immune disorder or cancer. However, there is a growing demand for novel small-molecule IFN inducer due to tolerance, toxicity, or short duration of action following direct administration of IFNs. In this study, we assessed arylpiperazine (ARP) as a new core skeleton of IFN inducer. To investigate structure–activity relationship, we designed and synthesized a series of ARP analogues and evaluated the ability to stimulate IFN response in THP-1 human monocyte cells. Compound 5i was identified as a potent type I IFN inducer as it significantly increased cytokine secretion and increased expression of various IFN-stimulating genes which are representative biomarkers of type I IFN pathway. Our results suggested a beneficial therapeutic potential of 5i as an anti-viral agent.
Keywords: Drug Design; Humans; Immunity, Innate; Interferon Inducers; Interferon Type I; Monocytes; Piperazines; THP-1 Cells; Anti-viral agent; Arylpiperazine; Innate immunity; Interferon inducer; type I Interferon